Adherence to Organisational Ethics as a Factor for Facilitating Employees' Performance in the Workplace - Surulere, Omosuyi Julius Surulere; Ige, Folasade Folakemi Ige; Owokalu, Olufemi Owokalu; Owolabi, Oluwapelumi Bunmi Owolabi (African Journal of Stability and Development (AJSD), 2025)
The study examined the link between organisational ethics and employee performance, and how organisational support influences this relationship. The paper investigated how ethical leadership, organisational culture, employee participation, and compliance with ethical principles affect productivity, job satisfaction, and organisational outcomes. A quantitative ex-post facto design was used, analysing data from 500 organisations in Nigeria from 2012 to 2024 through pooled regression analysis to assess both the direct and moderating effects of ethical conduct on performance. The findings showed that ethical leadership and organisational culture had the strongest influence on performance outcomes. While employee engagement and norm adherence had positive but modest effects, job satisfaction and organisational support were not strongly related to performance, and in some cases, not significantly so. Moreover, the results indicated that organisational support mediated the relationship between ethical leadership and workplace culture, thus enhancing the positive impacts of both on work outcomes. The interaction effects were significant, suggesting that when organisations provided appropriate resources, training, and incentives, ethical leadership and workplace culture became more powerful drivers of performance. Overall, this research highlights that moral leadership combined with effective support networks is essential to maximise workplace productivity. It concludes that maintaining a focus on high performance requires ongoing ethics and a robust institutional support system.